Influence of NH4F in Dextran Based Biopolymer Electrolytes: Conductivity and Electrical Analysis - Hamsan, Muhamad Hafiz; Zamani Kadir, Mohd Fakhrul; Aziz, Shujahadeen Bakar; Azha, Muhammad Amirul Solihin; Muzakir, Saifful Kamaluddin (Makara Journal of Technology, 2019)
Dextran polymer host was doped with different concentrations of ammonium fluoride (NH4F) via casting technique. In this present work, dextran-NH4F film has been employed to investigate the ionic conductivity using electrochemical impedance spectroscopy from 50 to 5 MHz. The highest room temperature conductivity is achieved at (2.33 ± 0.76) × 10-3 S cm-1 with 40 wt.% NH4F. The electrolyte is found to obey Arrhenius rule at high temperature with activation energy of 0.21 eV. Dielectric analysis has been performed to obtain better understanding on the conductivity pattern. The dielectric parameters e.g. ɛreal, ɛimag, Mreal, and Mimag have been tested as a function of frequency at various temperature. The potential stability obtained for the highest electrolyte in this study is 1.58 V.